Fenomena Hari Tanpa Bayangan Bulan Maret di Kota Medan - Habibullah Ritonga (University of Muhammadiyah Sumatera Utara, 2019)
A day without shadows is a day when the sun is right above (zenith), objects that are perpendicular to the sun and the entire plane of matter will be parallel to the direction of sunlight, so the object will not form a shadow around the object. This phenomenon occurs along with the artificial journey of the sun every year from south to north and vice versa from north to south. The sun will transit right above (zenith) cities in Indonesia. For the city of Medan, the phenomenon of days without bans is estimated to occur twice a year, namely every March 29 and October 2. This phenomenon occurs at midday, when the declination of the sun reaches 03 ° 34 ', equal to the value of the latitude of the city of Medan (03 ° 34' LU).